Tecnologias aplicadas em sistema de gestão ambiental: um modelo utilizando conceitos de economia circular em cadeias de suprimentos sustentáveis - Barbosa, Milton Augusto (Universidade Federal de São Carlos, 2025)
The successive agendas of the United Nations Organization for Global Sustainable Development seek sustainability and quality of life for human beings, balancing the environmental, social and economic pillars, projecting that future generations can continue to consume resources, products and services respecting the limits of planet Earth. Thus, knowing that industrial manufacturing processes and, consequently, the disorderly consumption of products and services generate adverse impacts on planet Earth, countries need to put projects and goals into action to achieve global sustainability. Thus, some goals can be achieved with the application of Technologies in Environmental Management Systems (EMS) using Circular Economy (CE) concepts in Sustainable Supply Chains (SSC). Innovating and contributing to reduce adverse impacts, this thesis aims to demonstrate the application of technologies for sustainability and propose an EMS model based on EC pillars in SSC, with the support of declarative software, from the conception of the product/service development to the end of the product/service life cycle. The methods and materials developed were applied bibliographic research and methodological research with interventionist investigation. The research results present several opportunities for studies in I4.0 technologies to be applied by similarity in the environmental area, deepen the knowledge of the actions necessary for the real application of CE, provide the use of information for environmental education with CE principles, develop knowledge for society, government and companies to jointly develop CE legislation, create opportunities for analysis and application of EMS model based on CE pillars, enable the development, through professional multidisciplinary, the use of digital to support EMS, integration of technologies in sustainable supply chains for continuous improvement of processes and validation of software for analysis of environmental aspects and impacts with circular actions in supply chains.
Technologies applied in environmental management systems: a model using circular economy concepts in sustainable supply chains
Tecnologías aplicadas en sistemas de gestión ambiental: un modelo que utiliza conceptos de economía circular en cadenas de suministro sostenibles
Keywords: ESG; Industria 4.0; ISO 14001; Produção Circular; Sustentabilidade; Industry 4.0; ISO 14001; Circular Production; Sustainability; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; CIENCIAS SOCIAIS APLICADAS